What can be learnt from the 2018 drought and how to adapt Swedish agriculture to a changing climate? : an exploratory study with farmers from Mälardalen - Rende, Serafima (SLU/Dept. of Urban and Rural Development, 2019)
In 2018, the unusually dry and hot summer caused large losses in agricul-tural production. Farmers in Mälardalen had to struggle all summer to gather enough animal fodder, working long hours but gaining little in return. Climate change poses a threat to agricultural production because it is sensi-tive to weather extremes and weather fluctuations makes it harder to adapt to a changing climate. This study aims to explore how drought affected farmers in Mälardalen in 2018. What kind of adaptive strategies did they ap-ply? If and how do farmers prepare and plan for climate change? Are there any opportunities or is climate change only negative? How do farmers think about adaptive management on their farms and what are the challenges to its implementations? The information was collected through semi-structured interviews with five farmers, two farmers’ organizations and county board administration from two counties. The findings show that the context plays a crucial role for farmers’ adaptability and that every farmer’s situation is unique. This also affects their decisions and strategies of adaptive manage-ment.